The Death Sentence for Covid-19 Financial Fraud Perpetrators - Nelvitia Purba; Muhammad Arif Sahlepi; Sri Sulistyawati (Sriwijaya Law Review, 2020)
Coronavirus pandemic 2019-2020 or known as Covid-19, which spread throughout the world, including Indonesia, has caused casualties and disrupted the economy. Various attempts were made by the government to overcome the increasingly massive impact of the spread of Covid-19. One of them is by issuing the Government Regulations in Lieu of Laws No. 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling Covid-19 Pandemic. Regarding this assistance provided by the government, it is miserable to have allowed the occurrence of criminal acts of corruption committed by government officials and their instruments. The purpose of this paper is to pay attention to the handling and eradication of corruption of Covid-19 Pandemic aid funds. The method used in this paper is to analyze data qualitatively in relation to this research which is a normative juridical type. The data used are primary and secondary data obtained through the search of legislation and materials related to the issues raised. As a result, this article argues that when there have never been cases of corruption whose actors have been sentenced to death in a normal situation, it might be possible for the misuse of the Covid-19 pandemic aid funds can be sentenced to death.